2015
DOI: 10.1080/00140139.2015.1013576
|View full text |Cite
|
Sign up to set email alerts
|

Designing a ticket to ride with the Cognitive Work Analysis Design Toolkit

Abstract: The Cognitive Work Analysis Design Toolkit has been developed to provide ergonomics practitioners with a structured approach for translating the outputs of cognitive work analysis into design solutions. This paper demonstrates an application of the toolkit and provides evaluation findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Materials from a systems thinking-based design toolkit (Read et al, 2015), originally developed for use with the Cognitive Work Analysis (CWA) framework (Vicente, 1999), were adapted for use with the AcciMap analyses. The toolkit provides a structured approach for translating the outcomes of systems analysis methods into design concepts.…”
Section: Methodsmentioning
confidence: 99%
“…Materials from a systems thinking-based design toolkit (Read et al, 2015), originally developed for use with the Cognitive Work Analysis (CWA) framework (Vicente, 1999), were adapted for use with the AcciMap analyses. The toolkit provides a structured approach for translating the outcomes of systems analysis methods into design concepts.…”
Section: Methodsmentioning
confidence: 99%
“…As a step toward helping to close this gap, we developed a design approach called the CWA‐DT (Read, Salmon, & Lenne, ; Read, Salmon, Lenné, & Jenkins, ). The purpose of the CWA‐DT is to provide an approach for translating the outputs of CWA into design recommendations.…”
Section: Cognitive Work Analysismentioning
confidence: 99%
“…The initial call was put forward by Vicente (2002) in his review of ecological interface design and reiterated by Naikar (2012) in relation to discussions of team design. Since then, Read et al (2015) have reported a case study in which CWA was used in combination with a template requiring design features associated with multiple elements to be documented. While it seems that such a template could help ensure that designs of multiple elements are considered concurrently, the findings of the case study suggest that this is not a guaranteed result.…”
Section: Systemmentioning
confidence: 99%